2013
DOI: 10.1097/ico.0b013e3182a7387f
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Corneal Thickness Using Dual-Scheimpflug Imaging at Different Stages of Keratoconus

Abstract: The data obtained by dual-Scheimpflug imaging for the corneal thicknesses of the entire cornea provide useful information for grading the severity of keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Wolffsohn et al and Demir et al also found a negative correlation between stage of keratoconus and corneal thickness [22, 23]. In our study all of the subgroups showed significantly high correlations between measurements of the 2 devices ( P < 0.001) and the greatest difference was at the CT 8 mm in all stages of keratoconus.…”
Section: Discussionsupporting
confidence: 70%
“…Wolffsohn et al and Demir et al also found a negative correlation between stage of keratoconus and corneal thickness [22, 23]. In our study all of the subgroups showed significantly high correlations between measurements of the 2 devices ( P < 0.001) and the greatest difference was at the CT 8 mm in all stages of keratoconus.…”
Section: Discussionsupporting
confidence: 70%
“…Detection of corneal ectatic disorders as early on as possible is necessary to prevent, or delay, the progression of keratoconus. Some studies claim to distinguish SCKC from normal eyes using topographic parameters [ 34 , 35 , 36 ] and others state that there is an overlap between topographic data obtained from a SCKC group and a normal group [ 37 , 38 ]. As a result, biomechanical data could improve the detection and severity prediction of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…The Pentacam Scheimpflug camera asseses the curvature and elevation of the anterior and posterior corneal surface as well as pachymetry with high reproducibility and repeatability [11] , [12] . Several studies have proved high accuracy of posterior elevation measurements in detecting keratoconus [13] [17] and some reported pachymetry as a sensitive parameter to detect progressive changes in keratoconus [18] [24] . In addition, relational thickness profile was found to be superior to single-point pachymetric data in discriminating normal corneas from those with keratoconus [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%